A hybrid modeling framework for the investigation of surface roughening of polymers during oxygen plasma etching. (16th February 2021) - Memos, George; Lidorikis, Elefterios; Gogolides, Evangelos; Kokkoris, George
Abstract: Oxygen and oxygen-containing plasmas offer great potential for the surface functionalization of polymeric substrates: thermal reactive neutral species are combined with high energy ions to alter both the micro/nanomorphology and composition of polymeric surfaces in a dry process. Although plasma processing is an attractive option for polymer surface modification, plasma–surface interactions are complex and the process design is usually based on a trial-and-error procedure. Toward a comprehensive process design, a hybrid modeling framework, addressing both effects of plasmas on polymeric surfaces, is developed and applied to an investigation of the oxygen-plasma-induced surface roughening of poly(methyl methacrylate). A kinetic Monte Carlo surface model, considering the synergy of neutral species and ions, is used for the calculation of the local etching rate. The novel element of the model is that it takes into account the surface morphology through the calculation of the trajectories of the species joining the surface reactions. The local etching rate is utilized by a profile evolution module based on the level set method to predict the surface roughness evolution. A method for tracking the local variables of the evolving surface profile (e.g. surface coverage), treating a fundamental weakness of the level set method, is proposed and used to effectively reduce the computational time. The results of the framework are validated by comparison to a theoretical model. The prediction of roughness evolution is consistent with measurements vs time and at different operating conditions. The potential of the framework to additionally handle the chemical composition (oxidation) of the surface is demonstrated, enabling the study of the wetting behavior of plasma-etched polymeric surfaces.